Association between war-related traumatic events and blood pressure trajectory: a population-based study among the mid-aged and older Palestinian adults living in Gaza - Jebril, Majed; Mazidi, Mohsen; Liu, Xin; Baibing, Mi; Arafat, Heba; Shi, Zumin; Wang, Youfa (Frontiers in Public Health, 2023)
Abstract Background Little is known regarding health status in an environment characterized by instability and ongoing war risks. This study investigated hypertension disease burden and associations of war-related traumatic events with blood pressure (BP) trajectory over time amongst mid-aged and older Palestinian adults in Gaza Strip. Methods From nine primary healthcare centers, medical records between 2013 and 2019 were collected for 1000 mid-aged and older Palestinian adults living in Gaza. Multinomial logistic regression analysis examined associations between war-related traumatic events and BP trajectories derived using latent class trajectory analysis (LCTA). Results The prevalence of self-reported injury (of participants or their family members), death of a family member, and violence due to house bombing was 51.4%, 54.1%, and 66.5%, respectively. In total, 22.4% and 21.4% of participants had constant-very-high (CVH) systolic BP (SBP) (>160 mmHg) and diastolic BP (DBP) (>95 mmHg), and normal-stable SBP and DBP was found only 54.9% and 52.6%, respectively. Injury (participants or family members), death of a family member, and violence due to house bombing during wars were associated with CVH SBP with odds ratios [95 CI, OR=1.79 (1.28-2.48), 1.90 (1.36-2.65), and 1.44 (1.01-2.05)], respectively. The corresponding figures were [95 CI, OR= 1.92 (1.36-2.71), 1.90 (1.35-2.68), and 1.62 (1.13-2.38)] for CVH DBP. Living in debt was positively associated with CVH SBP, [95 CI, OR= 2.49 (1.73-3.60)] and CVH DBP, [95 CI, OR= 2.37 (1.63-3.45)]. Conclusion The disease burden related to war-related traumatic events is high and positively related to adverse BP trajectory among the mid-aged and older Palestinians living in Gaza. Intervention programs are needed to manage and prevent chronic diseases in this vulnerable population. Funding This research was funded in part by the US-based China Medical Board (CMB, grant number 16-262); National Natural Science Foundation of China, grant number 82173504, 82011530197; and the Chinese National Key Research and Development Program (grant number 2017YFC0907200, 2017YFC0907201). Keywords Blood pressure, Palestine, Traumatic event, War event